Potential and Absorption of CO2 in Various Types of Dry Land Use in Aceh Besar Regency - Abdullah, Umar Husein; Martunis, Lukman; Mulyanti, Mulyanti; Yana, Dewi; Akbar, Yusran; Agustina, Sri (Journal of Agriculture, 2024)
This study was carried out on a 239,439.63 ha unit of dry land in the Aceh Besar Regency. The Soil and Plant Science Laboratory and the Soil Physics Laboratory at the Faculty of Agriculture, Universitas Syiah Kuala, analyzed soil and biomass samples. Twelve different land use types in the Aceh Besar Regency's dry land are the research locations. Utilizing a methodology with the number SNI 7724:2011, the Indonesian National Standards Agency established the biomass measuring and sampling procedure in 2011. According to the study's findings, the primary forest land use type has the greatest potential for absorbing CO2 in the forest land use type, followed by the following. Pine forest, secondary forest, teak forest, eucalyptus forest, and bush forest, in that order. In contrast, the land use categories of mixed gardens, moors, bushes, grassland, rainfed rice fields, and bare ground have the highest potential for absorbing CO2. Primary forests have the largest overall carbon dioxide absorption among the many forest land use types. These are followed, in order, by secondary forests, bush forests, eucalyptus forests, pine forests, and teak forests. The primary forest land use type has the largest total CO2 absorption among the non-forest land use types, followed by grasslands, shrubs, mixed gardens, rainfed rice fields, moorland, and bare ground, in that order. The Aceh Besar Regency's numerous dry land uses can benefit from enhanced natural and environmental sustainability due to the wide stem diameter and abundance of woody plants, which can also increase CO2 absorption. Highlights High CO2 potential and sequestration are critical in controlling climate change Humans play an important role in regulating and maintaining the availability of plants to maintain environmental stability. Forest protection plays an important role in maintaining the biodiversity of plants, animals, and endangered species in protected forest areas.